Sulfur-acetylacetone based solutions for precipitation of quasi-core-shell microparticles or hybrid structures - Zaman, Ali Can (ELSEVIER, 2022)
A methodology to produce quasi-core-shell or hybrid microstructured sulfur particles is introduced in this study. Dissolution of sulfur in acetylacetone (AcAc) suspensions at high temperatures and recrystallization upon cooling enables production of quasi-spherical carbon-sulfur composites or carbon nanotube (CNT)/graphite encapsulated sulfur particles. Particle sizes are in the range of several micrometers in all cases. The particle formation mechanism relies on temperature dependent solubility of sulfur in AcAc. AcAc provides dissolution of sulfur at relatively high quantities (greater than25 g L-1), and it also allows homogenous dispersion of nanoparticles. This medium provides interaction of sulfur crystallites with carbon particles during recrystallization in colloid. Several techniques were employed to elucidate the solubility behavior of sulfur in AcAc and structure of composites including fluorescence spectroscopy, dynamic light scattering (DLS) and atomic force microscopy (AFM). It was found that sulfur presents in the form of homocyclic rings in AcAc near room temperature under ambient pressure as verified through assignments using UV-Visible absorption (UV-Vis) and Raman spectroscopy techniques. This study has wide implications. Because exploitation of high solubility of sulfur in polar and nonvolatile solvents may provide new opportunities for composite particle production with tailored properties. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: Sulfur; Core-shell; Composite; Carbon nanotube, colloid, solution, processing; CARBON QUANTUM DOTS; ELEMENTAL SULFUR; CATHODE MATERIAL; DYE REMOVAL; LITHIUM; ACID; LI; ESTERIFICATION; POLYSULFIDES; DISSOLUTION; Chemistry; Physics